LOYALITAS WISATAWAN DAMPAK KEPUASAN WISATAWAN, PROMOSI DAN SADAR WISATA MASYARAKAT PULAU TIDUNG (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2021)
Tidung Island is one of the islands in the Thousand Islands and has become a tourist attraction for visitors to enjoy panoramic views, water tourism and underwater reefs. Local people take advantage of this opportunity to be managed independently in an effort to support the tourism potential in their area. This study aims to analyze the loyalty of tourists visiting Tidung Island due to the influence of tourist satisfaction which is supported by promotion and awareness of community tourism. The data used in this study are primary data obtained from questionnaires. The number of samples of 200 respondents using descriptive quantitative purposive sampling method. The data analysis technique used path analysis. The results showed that promotion and awareness of community tourism had a positive and significant effect on tourist satisfaction. Tourist satisfaction has a positive and significant effect on tourist loyalty. Promotion and awareness of community tourism have a positive and significant effect on tourist loyalty.Â Keywords: promotion, awareness of community tourism, tourist satisfaction, tourist loyalty.